2011
DOI: 10.1097/fpc.0b013e32834b6918
|View full text |Cite
|
Sign up to set email alerts
|

Two minor NQO1 and NQO2 alleles predict poor response of breast cancer patients to adjuvant doxorubicin and cyclophosphamide therapy

Abstract: This study suggests that both NQO1 and NQO2 modulate the efficacy of AC therapy and that NQO2 is associated with tamoxifen toxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(26 citation statements)
references
References 32 publications
2
24
0
Order By: Relevance
“…A polymorphism of NQO1 has reportedly been associated with response to chemotherapy (47,48). Therefore the existing data indicated that confirmation of genetic background prior to β-lap treatment would be warranted for patients with malignant melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…A polymorphism of NQO1 has reportedly been associated with response to chemotherapy (47,48). Therefore the existing data indicated that confirmation of genetic background prior to β-lap treatment would be warranted for patients with malignant melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…This simple genetic test may be a more practical measure of the influence of NQO1 on quinone drug activation since this test would identify NQO1-null individuals. Complicating the association between the NQO1*2 polymorphism and response to chemotherapy are studies in women with breast cancer that have demonstrated an association of the NQO1*2 polymorphism with decreased survival in patents receiving anthracycline therapy [116, 117], however, in these studies the role of NQO1 in survival is believed to be linked to its role in p53 stabilization and or modulation of TNF-alpha and not through drug activation [116]. …”
Section: Nqo1 In the Clinicmentioning
confidence: 99%
“…It also binds 60 to the tumour suppressor protein p73 and the polyamine biosynthesis 61 pathway enzyme ornithine decarboxylase [17,18]. NQO1 interacts 62 with the 20S proteasome reducing its activity, preventing it from 63 degrading these proteins; however, partially unfolded forms of NQO1 64 can be efficiently degraded by the 20S proteasome [19]. showing the location of Arg139 and Pro187.…”
Section: Nad(p)hmentioning
confidence: 99%